Reliability-based Design Optimization of Classical Wing Aeroelasticity - S Sleesongsom; S Yooyen; P Prapamonthon; S Bureerat (My University, 2020)
Abstract Flutter speed of aircraft is very important and needs to be firstly specified before a certification applied for a new aircraft by airworthiness regulator to make sure that the aircraft is free from flutter in its flight envelope. By assuming geometrical and physical parameters known, the speed is usually estimated from deterministic analyses in a design stage. In practice, some parameters are finitely measured by observing, especially for the geometrical parameters, material properties and so on due to the random in nature, which causes uncertainty of information often called uncertainties. The purpose of this paper is to combine reliability analysis and optimum design of aeroelastic aircraft wing. The classical two-dimensional wing with a typical airfoil section is used as an example in this study. To quantify uncertainty in the design of flutter speed, the discrete-time aero-elastic model and worst-case scenario are applied. Furthermore, the comparison between optimum design with/without reliability is provided in this study. The results show the proposed technique leads to the flutter speed being more conservative and realizable compared with the traditional technique.
Keywords: Aeroelasticity; Flutter; Flight envelope; Envelope (radar); Probabilistic and Robust Engineering Design